Casa Abierta de Terapia Física - Llivi Ruilova, Danny Vicente (2023)
The Open House, organized by the UEB Physical Therapy major, was successfully completed in honor of the “Ecuadorian Physiotherapist Day”; the same one that had the presence of Mgtr. Silvana López Paredes, Dean; Mgtr. Washington Fierro, director of Academic Management; Mgtr. Cynthia Pilco Toscano, head of the course and teaching staff.